2021
DOI: 10.37268/mjphm/vol.21/no.3/art.1093
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Compliance With Smoke Free Laws in Batu Buruk, Terengganu: A Direct Observation

Abstract: Batu Buruk beach has been gazetted as a non-smoking zone by the Minister of Health under the initiative of Terengganu state government via their program known as ‘Terengganu Bebas Asap Rokok’ (TBAR). The smoking bans at Batu Buruk was enforced in order to preserve and protect the public from the dangers of cigarette smoke as well as to keep the city's environment clean and healthy. The objectives of this study were to assess the status of compliance to legislation and identify the potential aspects of violatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…We found that study participants aged greater than 34.7 years were 2 times more likely to have unsuccessful treatment outcomes than those aged ≤34.7. This finding agrees with the results of studies conducted in Tigray, Ethiopia, 24 Arba Minch, Ethiopia, 25 Eastern Ethiopia, 14 South Africa, 26 Malaysia, 17 and China. 27 The plausible rationale might be that older people frequently have comorbid ailments, have overall physiological decline with age, and are less able to access health care services.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that study participants aged greater than 34.7 years were 2 times more likely to have unsuccessful treatment outcomes than those aged ≤34.7. This finding agrees with the results of studies conducted in Tigray, Ethiopia, 24 Arba Minch, Ethiopia, 25 Eastern Ethiopia, 14 South Africa, 26 Malaysia, 17 and China. 27 The plausible rationale might be that older people frequently have comorbid ailments, have overall physiological decline with age, and are less able to access health care services.…”
Section: Discussionsupporting
confidence: 91%
“…Older age, residence, concomitant conditions, a lack of contact person, a sputum smear-negative treatment category at the start of therapy, and HIV-positive status were all linked to poor TB treatment outcomes. 14,17,18 While family support, socioeconomic, physician and nurse support, availability to access health services, social stigma, psychological stress, and knowledge were significant factors in the successful treatment of tuberculosis. 16,[18][19][20][21][22] In Ethiopia, a standardized TB prevention and control program incorporating Directly Observed Treatment, Short Course (DOTS) was started as a pilot in 1992, at the Arsi zone in the Oromia region.…”
Section: Introductionmentioning
confidence: 99%